Effects of Learning Facilities and School Environment through Self-regulation on the Learning Interests of Primary School Students - Rahmani Riyadi, M Ilham; Sutarto, Joko; Yusuf, Amin (Universitas Negeri Semarang, 2021)
Interest in learning is an important aspect for students in the teaching and learning process. Student learning interest arises influenced by various factors including learning facilities, the school environment and self-regulation. The purpose of this study is to determine the effect of learning facilities and the school environment through self-regulation on the learning interests of elementary school students. This research is a correlational study with a cross sectional study approach. There were 138 students taken as sampling from the total population. The instrument used was a questionnaire and data analysis was performed statistically, with multiple regression test. The results showed that learning facilities affect student learning interest. The school environment influences student interest in learning and self-regulation moderates the influence between learning facilities and the school environment on student interest in learning.